Revealing Competitiveness and Key Drivers of Nickel (HS 75) Exports: Evidence from Seven Major Destinations, 2014–2023 - Siahaan, Vendredy P. Lucasio; Kartiasih, Fitri (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
The downstream policy is implemented to encourage Indonesia’s processed nickel products. Processed nickel under Harmonized System (HS) 75 is a value-added product that has potential for the Indonesian economy. Globally, Indonesia’s exports of nickel HS 75 have increased significantly. This increase occurred after the implementation of the downstream policy. However, the increase in export volume did not occur uniformly across all trading partner countries, hence further analysis of the implemented downstream policy is necessary. This study aims to analyse the effect of the down streaming policy and macroeconomic variables such as the destination country’s GDP per capita, real prices, exchange rate, and the RCA index significantly affect the export volume of nickel (HS 75), while population and the downstream policy do not have significant effect. These findings indicate that the downstream policy has not yet effectively increased export volumes to trading partner countries.